The Role Foreign Direct Invesment, Financial Development and Institutions Quality of Economic Growth Empirical Evidence From WANA Countries - Muhammad Ahsanul Amal; Muhammad Ghafur Wibowo (Journal of Business Management and Islamic Banking, 2024)
Research Aims: The study investigates the impact of foreign direct investment, financial development, and institution quality on economic growth in nations located in western Asia and North Africa Methodology: This study methodology employs a panel data regression model using a fixed effect model (FEM) strategy. The study data is collected using the information that was available between the years 2000 and 2022. The WANA nations include Saudi Arabia, Iran, Israel, Jordan, Kuwait, Lebanon, Morocco, Egypt, Oman, Qatar, Tunisia, and the United Arab Emirates. Research Findings: The findings indicated that foreign direct investment (FDI), financial development (FD), and intellectual quotient (IQ) had an impact on economic growth. Specifically, foreign direct investment (FDI) has a beneficial and statistically substantial impact on economic development, but the quality of institutions has an adverse and statistically substantial impact on economic growth. However, financial development does not affect economic growth. Originality: The grand theory used in this research Economic Growth, Foreign Direct Investment, Institutions Quality, Financial Development, and Export and population growth variables are controlled. variables in this study by testing three variables consisting of independent variables, dependent variables and control variables. Research limitation and implication: The findings in this study suggest that policies implemented by governments, public institutions and academics aimed at increasing FDI, FD, and institutional quality can help improve economic growth in WANA countries.